Oculomotor Performances Are Associated With Motor and Non-motor Symptoms in Parkinson's Disease - Zhang, Yu; Yan, Aijuan; Liu, Bingyu; Wan, Ying; Zhao, Yuchen; Liu, Ying; Tan, Jiangxiu; Song, Lu; Gu, Yong; Liu, Zhenguo (Frontiers in Neurology, 2018)
Background: PD patients exhibit deficits in oculomotor behavior, yet the results are inconsistent across studies. In addition, how these results are associated with clinical symptoms is unclear, especially in china. Methods: We designed a case-control study include 37 PD patients and 39 controls in China. Clinical manifestations of PD patients were collected. Oculomotor performance was measured by a video-based eye tracker system. Results: We found that six oculomotor parameters including fixation stability, saccadic latency, smooth pursuit gain, saccade frequency, viewing range and saccade frequency during free-viewing context, were significantly different between PD patients and control group. Combining all the six parameters could reach a correct rate as high as above 90% for diagnostic accuracy. Moreover, the Pursuit gain was significantly associated with PD duration, UPDRS Ⅲ, in PD patients. The saccade latency was significantly associated with PD duration, Berg balance score, RBD score and Total LEDD in PD patients. Conclusions: PD patients commonly exhibit oculomotor deficits in multiple behavioral contexts, which are associated with both motor and non-motor symptoms. Oculomotor test may provide a valuable tool for PD clinical assessment.